2010
DOI: 10.1158/0008-5472.can-09-3541
|View full text |Cite
|
Sign up to set email alerts
|

Single-Nucleotide Polymorphisms Inside MicroRNA Target Sites Influence Tumor Susceptibility

Abstract: Single-nucleotide polymorphisms (SNP) associated with polygenetic disorders, such as breast cancer (BC), can create, destroy, or modify microRNA (miRNA) binding sites; however, the extent to which SNPs interfere with miRNA gene regulation and affect cancer susceptibility remains largely unknown. We hypothesize that disruption of miRNA target binding by SNPs is a widespread mechanism relevant to cancer susceptibility. To test this, we analyzed SNPs known to be associated with BC risk, in silico and in vitro, fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
274
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 344 publications
(286 citation statements)
references
References 32 publications
10
274
0
2
Order By: Relevance
“…Recently in a Chinese study, BRCA1 (rs799917) was found to be associated with breast cancer risk (Huo et al, 2009). Nicoloso et al (2010) found that a codon SNP (rs799917) in BRCA1 gene, which is predicted to be a binding site for miR-638, was associated with increased risk of breast cancer and germline occurrence of BRCA1 (rs799917) significantly varies among populations with different risks of developing breast cancer. Cox et al (2005a) also have reported the association of BRCA1 (rs799917) with breast cancer, but Sehl et al (2009) showed a lack of association between the BRCA1 (rs799917) and breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recently in a Chinese study, BRCA1 (rs799917) was found to be associated with breast cancer risk (Huo et al, 2009). Nicoloso et al (2010) found that a codon SNP (rs799917) in BRCA1 gene, which is predicted to be a binding site for miR-638, was associated with increased risk of breast cancer and germline occurrence of BRCA1 (rs799917) significantly varies among populations with different risks of developing breast cancer. Cox et al (2005a) also have reported the association of BRCA1 (rs799917) with breast cancer, but Sehl et al (2009) showed a lack of association between the BRCA1 (rs799917) and breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…As the majority of these miRNAs binds to the 3'UTR region of the genes (Sehl et al, 2009), variations in the 3'UTR regions of BRCA1/2 may also affect the regulation of related proteins and thus response to the applied therapy (Nilsen, 2007). In addition, the importance of miRNA-binding site single-nucleotide polymorphisms (SNPs) of the BRCA1/2 genes in breast and ovarian cancer has been emphasized in recent studies of certain individual populations (Barroso et al, 2009;Pongsavee et al, 2009;Sehl et al, 2009;Kontorovich et al, 2010;Nicoloso et al, 2010;Joseph et al, 2011). However, knowledge about the effect of 3'UTR site variations of BRCA1/2 remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of miRNAs bind to target sequences located in the 3'UTR of mRNAs by base pairing, resulting in the cleavage of target mRNA or repression of their translation. When SNPs occur in the 3'UTR, they may modulate gene expression by altering miRNA target binding capacity, ultimately leading to DOI:http://dx.doi.org/10.7314/APJCP.2013.14.9.5037 Associations Between EFNA1 and Colorectal Cancer in Chinese differences in the disease susceptibility (Nicoloso et al, 2010). As predicted by TargetScan (http://www.targetscan.…”
Section: Discussionmentioning
confidence: 99%